Godzilla. King of the monsters [videorecording (DVD)] - Dougherty, Michael (Warner Bros. Home Entertainment ; Warner Bros. Entertainment Canada Inc., 2019)
The new story follows the heroic efforts of the crypto-zoological agency Monarch as its members face off against a battery of god-sized monsters, including the mighty Godzilla, who collides with Mothra, Rodan, and his ultimate nemesis, the three-headed King Ghidorah. When these ancient super-species, thought to be mere myths, rise again, they all vie for supremacy, leaving humanity's very existence hanging in the balance.